PENGARUH PENERAPAN PRINSIP-PRINSIP GOOD CORPORATE GOVERNANCE DAN BUDAYA TRI HITA KARANA PADA KINERJA KEUANGAN - Sastra, I Made Bhaskara; Erawati, Ni Made Adi (E-Jurnal Akuntansi; Vol 19 No 1 (2017), 2017)
This study aimed to examine the effect of the application of the principles of good corporate governance: transparency, accountability, responsibility, independency, fairness and culture tri hita karana (THK) on financial performance Lembaga Perkreditan Desa (LPD) Abiansemal district of Badung regency. THK culture in this study was measured using the indicator values ??contained therein, namely integrity, work ethic value and the value of environmental sustainability, while financial performance LPD views of profitability by using the ratio of return on assets (ROA). The sample in this research that the entire LPD in Abiansemal district of Badung regency with 34 sample and respective LPD chairman as respondent. Data analysis techniques used in this research is multiple linear regression analysis. Hypothesis testing results demonstrate the principles of transparency, accountability and culture THK partial significant positive effect on financial performance LPD, whereas principles, responsibility, independency and fairness no significant effect partially on financial performance LPD
Keywords: good corporate governance, transparency, accountability, responsibility, independency, fairness, tri hita karana, financial performance